Informer sans s’engager : modélisation de la dynamique énonciative dans les sujets d’actualité - Marie Chagnoux (Corela)
Through discourse attribution and modality mechanisms, newspeople can convey information without having to personally endorse what they are reporting. In some cases, they may even combine news from conflicting sources. We therefore provide a methodological framework aiming at detecting, locating and representing commitment as well as modality dynamics in texts, using discursive trees. In particular, the depth of a tree associated to a text illustrates the complexity of its reference frames. The purpose of this approach, more broadly, is to automatically exhibit contentious texts from any given corpus.